DESIGNING TEACHER PROFESSIONAL DEVELOPMENT FOR MATHEMATICS TEACHING WITH VARIATION THEORY - Ekawati, Rooselyna; Lin, Fou-Lai (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
In this study, we aimed at demonstrating the power of Variation Theory in exploring the localÃ‚Â situation of Indonesian teachers and Teacher Professional Development program. TheÃ‚Â projection of Variation theory regarding the enterprise of teaching results on the need ofÃ‚Â sensitivity of students and exemplary teaching strategy that differ with teachers teaching style.Ã‚Â Besides, It requires more opportunities for teachers to understand the critical feature of objectÃ‚Â of learning. By sequence of activity that elaborating variation theory and regards the localÃ‚Â situation might imply the improvement of students learning.Keywords: Variation Theory, Teacher Professional Development, IndonesiaÃ‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1497.127-137